Luminescence enhancement of a self-organised Y2O3:Eu3+ thin film-coated porous alumina membrane. Issue 39 (20th September 2016) - Abdellaoui, N.; Pereira, A.; Kandri, T.; Drouard, E.; Novotny, M.; Moine, B.; Pillonnet, A.
Abstract : Easy fabrication of a disordered photonic structure for fluorescence intensity amplification of a thin film deposited on a nanostructured membrane. Abstract : Y2 O3 :Eu 3+ thin films were deposited by pulsed laser deposition (PLD) on unordered porous alumina membranes (PAMs). We showed that by adjusting the deposition parameters, self-organisation of Y2 O3 :Eu 3+ on the PAM occurs, which leads to the formation of a disordered photonic structure with high index contrast. Luminescence measurements showed a strong enhancement of the red emission (up to 12 times) compared to a continuous layer. We demonstrated experimentally and theoretically that such luminescence enhancement is directly correlated to an increase of the absorption efficiency in the UV range.